Longevity of rain gardens in Minnesota (US) as a stormwater solution: a question of homeowner motivation and satisfaction - Jahnke, Linda B.; Barnes, Michael R. (Frontiers in Sustainable Cities, 2023)
Rain gardens are gardens with a specific purpose. Designed as a shallow depression that captures stormwater runoff from impervious surfaces, rain gardens are planted with deep-rooted, wet/drycycle tolerant plants that enable the water to slowly permeate and be filtered by the soil. They are used as stormwater best management practices by municipalities and organizations as part of their overall plans to meet water quality goals as mandated by the United States (US) Clean Water Act. City and watershed administrators are counting on these rain gardens to be durable, effective solutions for managing stormwater runoff. But when the rain gardens are installed in the yards of privately owned homes, control of these solutions lands on the homeowners' shoulders. How effective are the rain gardens years after installation? How do the social factors of motivation and satisfaction relate to the longevity of the rain gardens? The objective of this case study was to determine the perceived performance of residential rain gardens as well as homeowner motivation and satisfaction with them over time. Data was collected via an email survey from homeowners located in the Twin Cities of Minneapolis and St. Paul, Minnesota, US that had installed a rain garden. Key findings include 1) almost all rain gardens performed effectively, though some were not seen as successful, 2) motivations for installing rain gardens differ widely for successful versus challenged gardens and 3) satisfaction with the rain gardens decreases over time.